E-Cigarette or Vaping Use-Associated Lung Injury (EVALI): A Literature Review - Brahmantyo, Adhimas; Esha, Indi; Yunus, Faisal (Faculty of Medicine Universitas Airlangga, 2025)
Electronic cigarettes (e-cigarettes) are electronic tools designed to produce an inhalable aerosol from a liquid solution. Electronic cigarette or vaping use-associated lung injury (EVALI) describes any lung damage linked to the consumption of e-cigarettes or vaping products. The liquids and aerosols from e-cigarettes can include tobacco-related nitrosamines, aldehydes, metals, volatile organic compounds, phenolic compounds, polycyclic aromatic hydrocarbons, tobacco alkaloids from tobacco, flavor additives, and various medicinal compounds. Substantial evidence indicates that substances like propylene glycol, vitamin E acetate (VEA), and heavy metals such as lead and arsenic are significant constituents of e-cigarettes, contributing to lung harm. Patients with EVALI may present with sudden or gradually developing respiratory disease, presenting with non-specific signs, including breathlessness, coughing, chest discomfort, and sometimes coughing up blood. Radiological findings in EVALI are often non-specific. The most commonly observed pattern in EVALI is parenchymal organizing pneumonia (OP), identified in 56% of cases, whereby bilateral dominant ground-glass opacity (GGO) was identified, located in the inferior sections of the lungs or diffusely distributed with varying degrees of consolidation.